Development Of An Auricular Prosthesis Positioning Guide Using Additive Manufacturing Technologies - Heydenrych, André (Central University of Technology, 2020)
Facial deformities associated with congenital disorders or loss of facial features due to trauma or disease can have a devastating effect on the social well-being of a patient. This study focuses on deformed or missing auricles (ears) and their replacement with silicone prostheses. These prostheses are retained by craniofacial implants which are implanted into the temporal bone area of the skull in the appropriate position of the auricle. Surgeons find it difficult to place the implants accurately in relation to the missing auricle. The patient lies on their side on the operating table during the procedure and is largely covered by drapes to create a sterile working area. This makes it difficult to reference the position of the prosthesis, since the face and opposite auricle are covered. The aim of this study was to develop patient-specific devices using additive manufacturing technologies and associated software to indicate the positions of craniofacial implants which retain the auricular prostheses and to correctly orientate the prostheses relative to the positions of the implants. The geometry of the patient is determined using Computed-Tomography (CT) scanning and the opposite auricle is mirrored in the virtual environment through specialized software from Materialise. An iterative design process was followed to develop a positioning guide for placing the implants, with each design iteration improving on the previous one. In addition to the positioning guide, an orientation guide was developed that orientates the prosthesis accurately in relation to the implants. This is a new development in the field of maxillofacial prosthetics and has not been attempted before. The positioning/orientation guides are produced in nylon through the laser sinter additive manufacturing process. Craniofacial implants were developed and placed for patients in three case studies. The accuracy of placements was determined by CT scanning the area with the implants and overlaying the images onto the originally planned positions. Results showed relatively accurate positioning of the implants using the positioning guides, while reducing risk by not having to drill without reference points. The cost of the procedure is also reduced by shortening operating theatre time.
Dissertation